Plasma drug concentrations and virologic evaluations after stopping treatment with nonnucleoside reverse-transcriptase inhibitors in HIV type 1-infected children - Tim R. Cressey (2018)
Background. The optimum strategy for stopping treatment with drugs that have different half-lives in a combination regimen to minimize the risk of selecting drug-resistant viruses remains unknown. We evaluated drug concentrations in plasma, human immunodeficiency virus (HIV) load, and development of drug resistance after a planned treatment interruption of a nonnucleoside reverse-transcriptase inhibitor (NNRTI)-containing regimen in HIV type 1-infected children. Methods. Children with viral loads <50 copies/mL and CD4 cell percentages ≥30% (for children aged 2-6 years) or CD4 cell percentages ≥25% and CD4 cell counts ≥500 cells/μL (for children aged 7-15 years) were randomized to either a planned treatment interruption or to continuous therapy. In the planned treatment interruption arm, either (1) treatment with nevirapine or efavirenz was stopped, and treatment with the remaining drugs was continued for 7-14 days, or (2) nevirapine or efavirenz were replaced by a protease inhibitor, and all drugs were stopped after 7-14 days. Sampling for determination of plasma drug concentrations, measurement of viral load, and drug resistance testing was scheduled at day 0, day 7 (drug concentrations only), day 14, and day 28 after interruption of treatment with an NNRTI. Results. Treatment with an NNRTI was interrupted for 35 children (20 were receiving nevirapine, and 15 were receiving efavirenz). Median time from NNRTI cessation to stopping all drugs was 9 days (range, 6-15 days) for nevirapine and 14 days (range, 6-18 days) for efavirenz. At 7 days, 1 (5%) of 19 and 4 (50%) of 8 children had detectable nevirapine and efavirenz concentrations, respectively; efavirenz remained detectable in 3 (25%) of 12 children at 14 days. At 14 days, viral load was ≥50 copies/mL in 6 of 16 children interrupting treatment with nevirapine (range, 52-7000 copies/mL) and in 2 of 12 children interrupting treatment with efavirenz (range, 120-1600 copies/mL). No new NNRTI mutations were observed. Conclusions. In children with virological suppression who experienced interruption of treatment with an NNRTI, staggered or replacement stopping strategies for a median of 9 days for nevirapine and 14 days for efavirenz were not associated with the selection of NNRTI resistance mutations. © 2008 by the Infectious Diseases Society of America. All rights reserved.